Increased dispersion of refractoriness in the absence of QT prolongation in patients with mitral valve prolapse and ventricular arrhythmias. Issue 1 (January 1995) - Tieleman, R. G.; Crijns, H. J.; Wiesfeld, A. C.; Posma, J.; Hamer, H. P.; Lie, K. I.
Abstract : BACKGROUND--The mechanism responsible for the reported high incidence of ventricular arrhythmias in mitral valve prolapse is not clear. Electrocardiographic studies show an increased occurrence of repolarisation abnormalities on the 12 lead surface electrocardiogram, indicating regional differences in ventricular recovery. The purpose of this study was to investigate whether dispersion of refractoriness was an arrhythmogenic mechanism. METHODS--QT dispersion was measured in 32 patients with echocardiographically documented mitral valve prolapse and ventricular arrhythmias on 24 hour Holter recordings. QT dispersion was defined as the difference between the maximum and minimum average QT interval in any of the 12 leads of the surface electrocardiogram. QT dispersion corrected for heart rate was calculated by Bazett's formula. The results were compared with the data from 32 matched controls without a history of cardiac disease. Patients taking drugs that influence the QT interval and patients with a QRS duration > 120 ms were excluded. RESULTS--QT dispersion was greater in patients with mitral valve prolapse than in matched controls (60 (20) v 39 (11 ms) respectively, P < or = 0.001) as was corrected QT (64 (20 ms) v 43 (12 ms) respectively, P < or = 0.001). There was no significant difference in minimum or maximum QT intervals between the two groups. CONCLUSIONS--QT dispersion on the 12 lead surface electrocardiogram was greater in patients with mitral valve prolapse with ventricular arrhythmias than in normal controls, but the maximum QT interval was not increased. The results accord with the hypothesis that regional shortening and lengthening of repolarisation times in patients with mitral valve prolapse may account for the increased dispersion of refractoriness.